A case of prosthetic joint infection caused by Mycobacterium tuberculosis complicated secondary bacterial infection after knee joint replacement surgery. Issue 3 (March 2023) - Tachi, Yurika; Sato, Lubna; Ishikane, Masahiro; Yamada, Gen; Motohashi, Ayano; Ando, Honami; Hayakawa, Kayoko; Takasaki, Jin; Katsuragawa, Yozo; Ohmagari, Norio
Abstract: Mycobacterium tuberculosis ( M. tuberculosis ) is a rare cause of prosthetic joint infection (PJI). Previous studies have reported that many cases of PJI caused by M. tuberculosis have no medical history of active tuberculosis (TB) or other localization, which contributes to diagnostic difficulties. Furthermore, owing to the limited number of studies on treatment, appropriate treatment strategies, such as the duration of anti-tuberculosis ( anti -TB) drugs and surgical indications, remain unclear. We report a case of PJI caused by M. tuberculosis and secondary pyogenic arthritis caused by Staphylococcus aureus and Streptococcus dysgalactiae in a 67-year-old man after knee joint replacement surgery in Japan, which was a moderately endemic country until 2020 and a low endemic country since 2021. Although he had no past medical history or close contact with TB, he was diagnosed with PJI caused by M. tuberculosis, following the culture of a synovectomy specimen. He underwent two-stage surgery and was treated with anti -TB drugs for a total of 12 months and recovered without recurrence. Based on our case and previous studies, there are three points of clinical significance for PJI caused by M. tuberculosis . First, about one year of anti -TB drugs with two staged joint revision resulted in a good course of treatment. Second, surgical treatment might be considered in cases complicated by secondary bacterial infection. Third, because the diagnosis of PJI caused by M. tuberculosis is difficult, TB should be considered in the differential diagnosis of routine bacterial culture-negative PJI, especially in endemic areas.